State-of-the-Art of STEAM Education in Science Classrooms: A Systematic Literature Review - Yulianti Erni; Suwono Hadi; Abd Rahman Nor Farahwahidah; Phang Fatin Aliah (De Gruyter, 2024)
STEAM education is designed to prepare students for the twenty-first-century life skills and has been extensively investigated in the past 10 years. Given the rapid evolution of educational practices and the diverse ways in which STEAM is implemented in science classrooms, there is an urgent need for an analysis of the current outlook of STEAM education within the science classrooms context. In this article, 22 empirical studies were included to highlight the methodology, STEAM characteristics, and pedagogical approaches implemented in STEAM-based learning. Findings suggest that STEAM education plays an important role in fostering students' twenty-first-century skills and should be manifested by student-centered learning approaches. This study holds significant implications in providing direction for future studies regarding STEAM education in science classroom settings.